South Asian-Specific MYBPC3Δ25bp Deletion Carriers Display Hypercontraction and Impaired Diastolic Function Under Exercise Stress - Bazrafshan, Sholeh; Sibilia, Robert; Girgla, Saavia; Viswanathan, Shiv Kumar; Puckelwartz, Megan J.; Sangha, Kiranpal S.; Singh, Rohit R.; Kakroo, Mashhood; Jandarov, Roman; Harris, David M.; Rubinstein, Jack; Becker, Richard C.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: A 25-base pair (25bp) intronic deletion in the MYBPC3 gene enriched in South Asians (SAs) is a risk allele for late-onset left ventricular (LV) dysfunction, hypertrophy, and heart failure (HF) with several forms of cardiomyopathy. However, the effect of this variant on exercise parameters has not been evaluated. Methods: As a pilot study, 10 asymptomatic SA carriers of the MYBPC3Δ25bp variant (52.9 ± 2.14 years) and 10 age- and gender-matched non-carriers (NCs) (50.1 ± 2.7 years) were evaluated at baseline and under exercise stress conditions using bicycle exercise echocardiography and continuous cardiac monitoring. Results: Baseline echocardiography parameters were not different between the two groups. However, in response to exercise stress, the carriers of Δ25bp had significantly higher LV ejection fraction (%) (CI: 4.57 ± 1.93; p < 0.0001), LV outflow tract peak velocity (m/s) (CI: 0.19 ± 0.07; p < 0.0001), and higher aortic valve (AV) peak velocity (m/s) (CI: 0.103 ± 0.08; p = 0.01) in comparison to NCs, and E/A ratio, a marker of diastolic compliance, was significantly lower in Δ25bp carriers (CI: 0.107 ± 0.102; p = 0.038). Interestingly, LV end-diastolic diameter (LVIDdia) was augmented in NCs in response to stress, while it did not increase in Δ25bp carriers (CI: 0.239 ± 0.125; p = 0.0002). Further, stress-induced right ventricular systolic excursion velocity s' (m/s), as a marker of right ventricle function, increased similarly in both groups, but tricuspid annular plane systolic excursion increased more in carriers (slope: 0.008; p = 0.0001), suggesting right ventricle functional differences between the two groups. Conclusions: These data support that MYBPC3Δ25bp is associated with LV hypercontraction under stress conditions with evidence of diastolic impairment.